2023
DOI: 10.1186/s12964-023-01252-8
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix-induced signaling pathways in mesenchymal stem/stromal cells

Ekaterina Sergeevna Novoseletskaya,
Pavel Vladimirovich Evdokimov,
Anastasia Yurievna Efimenko

Abstract: The extracellular matrix (ECM) is a crucial component of the stem cell microenvironment, or stem-cell niches, and contributes to the regulation of cell behavior and fate. Accumulating evidence indicates that different types of stem cells possess a large variety of molecules responsible for interactions with the ECM, mediating specific epigenetic rearrangements and corresponding changes in transcriptome profile. Signals from the ECM are crucial at all stages of ontogenesis, including embryonic and postnatal dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 194 publications
0
7
0
Order By: Relevance
“…Cell differentiation is guided by several signaling networks, including WNT, BMP, TGFs, Hh, and FGF pathways. Development and maintenance of the heterogeneous components in the developing palate such as mineralizing bone, vasculature, nerves, epithelium, and cartilage likely not only involves coordinated signaling for lineage differentiation (Chen et al, 2021; Han et al, 2018; Novoseletskaya et al, 2023; Picoli et al, 2024; Tower et al, 2021), but must also include mechanosensitive elements. Thus, it is important to consider how changes in the mechanical environment following surgical intervention might alter the growth potential of the target tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Cell differentiation is guided by several signaling networks, including WNT, BMP, TGFs, Hh, and FGF pathways. Development and maintenance of the heterogeneous components in the developing palate such as mineralizing bone, vasculature, nerves, epithelium, and cartilage likely not only involves coordinated signaling for lineage differentiation (Chen et al, 2021; Han et al, 2018; Novoseletskaya et al, 2023; Picoli et al, 2024; Tower et al, 2021), but must also include mechanosensitive elements. Thus, it is important to consider how changes in the mechanical environment following surgical intervention might alter the growth potential of the target tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple integrins are abundantly found on the surface of many stem cell types. Subunit β1 is often linked to the stem cell phenotype as it aids in homing to the niche, maintaining stemness, and promoting proliferation [15]. In the case of MSCs, it has been shown that the interaction of human bone-marrow-derived MSCs (BMSCs) with type I collagen through α2β1 and α11β1 integrins promotes survival and proliferation [15,16].…”
Section: Msc Niche Components and Interactionsmentioning
confidence: 99%
“…Subunit β1 is often linked to the stem cell phenotype as it aids in homing to the niche, maintaining stemness, and promoting proliferation [15]. In the case of MSCs, it has been shown that the interaction of human bone-marrow-derived MSCs (BMSCs) with type I collagen through α2β1 and α11β1 integrins promotes survival and proliferation [15,16]. Aside from integrins, MSCs have also been shown to interact with ECM components through discoidin domain receptors, CD44, syndecans, and mechanosensitive ion channels [15].…”
Section: Msc Niche Components and Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These components are vital for cells to interface with their milieu, transmitting extracellular signals intracellularly. The dynamic and fluid nature of the plasma membrane allows cells to adapt to environmental changes ( 2 ) by interacting with the extracellular matrix ( 3 , 4 ), ligands ( 5 ) (e.g., cytokines and growth hormones), and neighboring cells (6). These interaction events are crucial in regulating signaling and driving cellular processes such as survival, proliferation, migration, or apoptosis ( 1 ).…”
Section: Introductionmentioning
confidence: 99%